On Working on Współczesny bajarz polski - Zuzanna Orlińska (Literatura Ludowa. Journal of Folklore and Popular Culture, 2023)
Zuzanna Orlińska - illustrator, author of texts for children and teenagers, among others, Ładna historia (A Nice Story, 2022), Okna Pałacu Saskiego (Windows of the Saxon Palace, 2022), Współczesny bajarz polski (A Contemporary Collection of Polish Folk Tales, 2021), Wstydu za grosz (No Shame, 2020), Miasto pamięci (A City of Memory, 2020), Matka Polka (Polish Mother, 2017), Ani słowa o Zosi (Not a Word about Zosia, 2020). She has received many awards and distinctions, including the “Guliwer w Krainie Olbrzymów” Award, the Kornel Makuszyński Literary Award and the award in the Astrid Lindgren Literary Competition